Guidelines Development Administration According to the Principles of good governance of Trang Provincial Lawyers Council - Lertworapat, Kriengkrai; Siriphornwut, Nattawat (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
The research aimed to 1) study the administration according to the principles of good governance of the Trang Provincial lawyer’s council; 2) study the problems and obstacles in the administration according to the principles of good governance of the Trang Provincial Lawyers Council and 3) identify ways to develop the administration according to the principles of good governance of the Trang Provincial Lawyers Council. By qualitative research. The 21 key informants’ selection was conducted through purposive sampling. Two semi-structured interview forms were used as research tools. In-depth interviews were conducted, and the data were analyzed through content analysis. The Research Results found that 1) The administration of the Trang Provincial lawyers council was in accordance with the Lawyers Act by adhering to the principles of good governance. 2) The problems and obstacles in the administration of the Trang Provincial Lawyers Council were caused by limited public relations regarding operations, which led to differences of opinion among members and a lack of cooperation. 3) Guidelines for the Development of Administration in Accordance with Good Governance Principles: 3.1) Lawyer Development: Training was needed to provide accurate knowledge to lawyer members, to foster positive attitudes and concepts, and to instill awareness of administration based on good governance principles. 3.2) Development of the Trang Provincial Lawyers Council: The administration of the Trang Provincial lawyers council needed improvement in alignment with the principles of good governance. There had to be enhanced public relations concerning operations and activities to educate lawyer members about good governance. Article history: Received 27 March 2025 Revised 1 September 2025 Accepted 3 September 2025 SIMILARITY INDEX = 14.33 %